2020
DOI: 10.1063/1.5143122
|View full text |Cite
|
Sign up to set email alerts
|

Formation and crystallographic orientation of NiSi2–Si interfaces

Abstract: The transport properties of novel device architectures depend strongly on the morphology and the quality of the interface between contact and channel materials. In silicon nanowires with nickel silicide contacts, NiSi2–Si interfaces are particularly important as NiSi2 is often found as the phase adjacent to the silicide–silicon interface during and after the silicidation. The interface orientation of these NiSi2–Si interfaces as well as the ability to create abrupt and flat interfaces, ultimately with atomic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…[ 33,39 ] For RFETs and other emerging devices an accurate control of phase formation becomes necessary as different phases and related lattice strain yield a variability in barrier heights and thus in the electronic injection properties. [ 40 ] Further on, phase instabilities lead to a junction patchiness that translates into additional variability of electrical performance. [ 41 ] Indeed, commonly employed metal‐silicides make the addition of further alloying elements such as for example, Pt or Sn in nickel‐silicides necessary to improve morphology and stabilize crystallographic phases.…”
Section: Introductionmentioning
confidence: 99%
“…[ 33,39 ] For RFETs and other emerging devices an accurate control of phase formation becomes necessary as different phases and related lattice strain yield a variability in barrier heights and thus in the electronic injection properties. [ 40 ] Further on, phase instabilities lead to a junction patchiness that translates into additional variability of electrical performance. [ 41 ] Indeed, commonly employed metal‐silicides make the addition of further alloying elements such as for example, Pt or Sn in nickel‐silicides necessary to improve morphology and stabilize crystallographic phases.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, SiNWs with relatively small diameters revealed anisotropic emerging electronic properties; these are quite interesting, given the industrial need for device miniaturization and the strong correlation between physical properties and sample sizes [25]. Specifically, this finding was in line with the synthesis of ultra-thin [001] SiNWs with diameters between 1.3 nm to 7 nm via an oxideassisted growth method, in which SiO powder was heated to 1200 • C in an alumina tube by Ma et al [27] or with transport measurements on SiNWs created along the [100], [111], or [110] directions [28].…”
Section: Introductionmentioning
confidence: 57%
“…In Schottky-barrier-FETs (SBFETs), the Schottky barrier height and interface quality depend on the phase of the silicide adjacent to the Si channel. 1,39 In this context, NiSi 2 is of special interest for SBFETs, as its Fermi level is near mid-gap in relation to the Si bandgap.…”
Section: Introductionmentioning
confidence: 99%
“…In Schottky barrier FETs (SBFETs), the Schottky barrier height and interface quality depend on the phase of the silicide adjacent to the Si channel. , In this context, NiSi 2 is of special interest for SBFETs, as its Fermi level is near midgap in relation to the Si bandgap. Moreover, it has a small lattice mismatch with Si, enabling the formation of an atomically abrupt Si–NiSi 2 interface with good crystalline quality. , In planar thin-film reactions, Tu et al reported the formation of NiSi 2 above 750 °C, while Tung et al demonstrated its formation at 450 °C.…”
Section: Introductionmentioning
confidence: 99%